2013
DOI: 10.1007/s13556-013-0003-9
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particle Profile of Fluticasone Propionate/Formoterol Fumarate Versus Other Combination Products: the DIFFUSE Study

Abstract: Introduction: The efficacy of inhaled products is affected by the degree, and potentially the site, of drug particle deposition in the lungs. Lung deposition correlates with the fine particle fraction (FPF; the proportion of dose containing particles \5 lm in aerodynamic diameter). This in vitro study (defining fluticasone propionate/ formoterol particulate size [DIFFUSE]) examined the effects of inhalation flow rate on the FPF of the fluticasone propionate/ formoterol (FP/FORM) pMDI aerosol compared with thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 32 publications
1
52
2
5
Order By: Relevance
“…At 60 lpm, the optimal inhalation flow with both DPIs, the MMAD, GSD and FPF of labeled dose were, respectively, 4.0, 2.0 and 15% for salmeterol and 3.7, 1.8 and 18% with fluticasone propionate. The MMAD, GSD and FPF of labeled dose were 2.5, 1.9 and 30% with formoterol and 2.5, 1.9 and 35% with budesonide [59]. These results are substantially in accordance with other previously known, where the average MMAD, GSD and Fine Particle Dose of labeled dose were, respectively, 3.5, 1.5 and 18% for salmeterol and 3.6, 1.5 and 20% with fluticasone propionate using the Diskus; and 3.3, 1.6 and 11% with formoterol and 3.1, 1.6 and 13% with budesonide using the Turbuhaler [61].…”
Section: Alternative Reliever Treatments Include Inhaled Anticholinermentioning
confidence: 89%
See 2 more Smart Citations
“…At 60 lpm, the optimal inhalation flow with both DPIs, the MMAD, GSD and FPF of labeled dose were, respectively, 4.0, 2.0 and 15% for salmeterol and 3.7, 1.8 and 18% with fluticasone propionate. The MMAD, GSD and FPF of labeled dose were 2.5, 1.9 and 30% with formoterol and 2.5, 1.9 and 35% with budesonide [59]. These results are substantially in accordance with other previously known, where the average MMAD, GSD and Fine Particle Dose of labeled dose were, respectively, 3.5, 1.5 and 18% for salmeterol and 3.6, 1.5 and 20% with fluticasone propionate using the Diskus; and 3.3, 1.6 and 11% with formoterol and 3.1, 1.6 and 13% with budesonide using the Turbuhaler [61].…”
Section: Alternative Reliever Treatments Include Inhaled Anticholinermentioning
confidence: 89%
“…It has been demonstrated that the percentage of respirable fraction contained in the aerosol (defined as drug particles with the diameter range between 2 and 5 μm) correlates with the drug deposition in lung tissues [57,58]. The inhaler used for the administration of the fluticasone propionate/ formoterol combination ensures the distribution of an aerosol with a respirable fraction of 40% of the inhaled dose [59], which is consistent at different inspiratory flows, with a plume value of 168 ms [60]. These characteristics facilitate drug deposition throughout the airways.…”
Section: Alternative Reliever Treatments Include Inhaled Anticholinermentioning
confidence: 99%
See 1 more Smart Citation
“…
We would like to clarify some points about the DIFFUSE (Defining fluticasone propionate/ formoterol particulate size) study (December 2013, p 39) [1] in light of the recent review by De Maria and colleagues [2]. Our in vitro study assessed the effects of inhalation flow rate on the aerodynamic particle size distribution Hence, the flow rate dependency of inhalers is of interest to physicians as well as regulators.
…”
mentioning
confidence: 99%
“…Hence, the plates were coated with surfactant when testing the two DPIs [1], as recommended by the European Pharmacopoeia. Coating may be not necessary for testing pMDIs [16,17] Moreover, the total amount of drug recovered from all stages, including from the ACI induction port, was within USP limits.…”
mentioning
confidence: 99%